2017
DOI: 10.5455/jice.20161204021732
|View full text |Cite
|
Sign up to set email alerts
|

Solving the puzzle: what is behind our forefathers’ anti-inflammatory remedies?

Abstract: Inflammation is a ubiquitous host response in charge of restoring normal tissue structure and function but is a double-edged sword, as the uncontrolled or excessive process can lead to the injury of host cells, chronic inflammation, chronic diseases, and also neoplastic transformation. Throughout history, a wide range of species has been claimed to have anti-inflammatory effects worldwide. Among them, Angelica sinensis, Tropaeolum majus, Castilleja tenuiflora, Biophytum umbraculum, to name just a few, have att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
(160 reference statements)
0
2
0
1
Order By: Relevance
“…Despite this, as we previously stated [ 16 ], a characterized compound with a perfectly defined mechanism of action at a particular dose fulfills the negative requirements (such as toxicity) inherited from classical pharmacology. However, new trends suggest an integrative approach in which a wide variety of compounds act on multiple targets together to produce a final action through a balance resulting from minor changes (synergy); something different is not expected here.…”
Section: Some Results Considerations Must Be Kept In Mind: Paving Tmentioning
confidence: 96%
“…Despite this, as we previously stated [ 16 ], a characterized compound with a perfectly defined mechanism of action at a particular dose fulfills the negative requirements (such as toxicity) inherited from classical pharmacology. However, new trends suggest an integrative approach in which a wide variety of compounds act on multiple targets together to produce a final action through a balance resulting from minor changes (synergy); something different is not expected here.…”
Section: Some Results Considerations Must Be Kept In Mind: Paving Tmentioning
confidence: 96%
“…To sum up, it must be concluded that not only is the pattern of gene expression (signature in some texts) different depending on whether a substance or a mixture of substances (extract) is administered, presumably more complex in the last case, but also depending on the substance/extract concentration or the extract fraction administered. The development and refinement of "-omic" technologies, including genomics/transcriptomics, proteomics, and metabolomics, has led to advances in the assessment of both the efficacy and, no less important, safety of herbal medicines [29,30] referred to by some authors as "herbomics", although this term is still in its infancy. An interesting study is the one published by Wang et al [31], in which the possible toxicological role of Matricaria chamomilla was evaluated using metabolomics approaches.…”
Section: The "-Omic" Technologies; Present and Futurementioning
confidence: 99%
“…A inflamação é uma resposta de defesa à infecção ou lesão tecidual, onde o organismo reage para localizar, inativar e destruir o agente agressor além de potenciar a reparação tecidual (Kulkarni et al, 2016;Villanueva et al, 2017).…”
Section: Inflamaçãounclassified